PENGARUH KUALITAS LAYANAN, KEPUASAN NASABAH DAN CITRA BANK TERHADAP LOYALITAS NASABAH BANK MUAMALAT DI SURABAYA - Evi Oktaviani Satriyanti (Journal of Business & Banking, 2012)
The business of banking in Indonesia today is developing very fast. This prompts competition among the banks to be higher and higher. The competition occurs when they attempt to attract the society interest so that these prospective customers are willing to become their customers. When bank products can be imitated easily, bank differentiation will no longet exist. Therefore, they should emphasize on their service quality. Service quality that given by a bank can attract the prospective customers to be loyal. When service quality is given its priority the banks already, fulfill service standard, so that the customers are satisfied. Later on, the customers will become loyal. This research tries to find to what extent the influence of service quality, customer satisfaction, and bank image influence the customer loyalty at Muamalat Bank in Surabaya. It was done by means of primary data taken by using questionnaire. The result of the research shows that service quality has positive and significant influence on customer loyalty which means that better service quality that given by Muamalat Bank to its customers so that the customers are loyal to Muamalat Bank, thus the loyalty is increased. Customer satisfaction has positive and significant influence on customer loyalty which means that the satisfied customers toward the service they received is also higher and this makes them more loyal to Muamalat Bank. The image of the bank also has positive and significant influence towards the customer loyalty, meaning that the more satisfied customers the more loyal they are.